Elisha Typology in Jesus' Miracle on the Jordan River (Papyrus Egerton 2, 2v.6-14) - Zelyck, Lorne R. (New Testament studies, 2016)
Previous reconstructions of the Miracle on the Jordan River' (Papyrus Egerton 2, 2v.6-14) are unconvincing because they lack clear parallels with known texts. This short article proposes a new transcription, based on the apparent parallels with Elisha's miracles in 2 Kings and Josephus, Jewish War 4.460-4. It concludes that the author of the Egerton Gospel used Elisha typology in the depiction of Jesus' miracle on the Jordan.